DINAMIKA INTERAKSI SOSIAL ANTARA SISWA BERKEBUTUHAN KHUSUS DAN SISWA REGULER DI SEKOLAH DASAR LABORATORIUM - Firly Ladiku; Lia Nurhayati; Fandi H. Binggo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to describe the dynamics of social interaction between students with special needs and regular students within the learning environment. The focus of the study was how social interaction processes were formed and developed in inclusive classrooms that involved students with differing characteristics. The study wasepted to provide an account of the patterns of social interaction occurring between students with special needs and regular students and to serve as a basis for developing more effective inclusive education practices at the elementary level. The research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation. The research subjects included the school principal, classroom teachers, students with special needs, and regular students involved in the inclusive classroom learning process. Data analysis followed the Miled and Huberman model, encompassing data reduction, data display, and conclusion drawing to obtain an in-depth understanding of the dynamics of social interaction occurring in the school setting. The findings indicated that the dynamics of social interaction between students with special needs and regular students developed progressively during classroom learning. This development was evidenced by five social interaction indicators: participation in collaborative activities, peer social support, social acceptance within the class community, initiave in reciprocal interactions, and positive emotional responses in peer relationships. The formed social interactions demonstrated processes of adaptation, cooperation, and mutual understanding between students with special needs and regular students, although some communication barriers and individual characteristic differences were still present. The role of teachers and an inclusive classroom environment were identified as crucial factors supporting the emergence of positive social interactions among students.